The problems of engineering education and training of engineering personnel in chemical technology in conditions of Russia’s WTO accession - G. S. Diakonov; V. G. Ivanov; V. V. Kondratyev (Высшее образование в России)
The paper reveals the challenges, which the engineering universities faced in conditions of Russia’s entry to World Trade Organization. There is shown the role of Kazan National Research Technological University as a creative space for innovative development of Russian engineering education and for training of engineering personnel of a new generation.